Implementasi Kuliah Kerja Nyata: Strategi Peningkatan Kualitas Melalui Pendamping Pendidikan Pengabdian Masyarakat - Itsna Shafia Chasana; Hanifia Risky Safitra; Rizqina Kautsarani Amira Putri; Ratna Muthia (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
The Community Service Program (KKN) in Purwokerto Village aims to improve the quality of education and support the development of students' character through various community service activities. The main activities carried out include Walisongo Teaching, an anti-bullying seminar, Ecoprint craft mentoring, additional tutoring, and teaching at the Darussalam TPQ. This program successfully created a conducive and interactive learning environment, while also strengthening moral and religious values among students. KKN students gained valuable experience in managing classes, implementing innovative teaching methods, and interacting with the local community. This program has had a positive impact on both students and the KKN participants, and it is hoped to continue with more varied innovations in the future.